Effect of different holding times of pasteurisation on Pseudomonas sp. count in goat milk - Adnan, Aminah (2017)
The distinctive goaty odour in goat milk is associated with lipolysis that occurs in the milk following milking. Lipolysis in milk is caused by several factors including the production of lipase from microbes in the milk. During pasteurisation, the number of bacteria is reduced but the enzyme may still remain. Pseudomonads can survive both laboratory and commercial pasteurization. Pseudomonas sp. that survives the treatment will proliferate further, especially after cooling and in storage condition. By increasing the holding time or holding period during pasteurisation, the presence of the bacteria can be reduced. The objectives of this study is to evaluate the bacteria colony count in goat’s milk after pasteurisation treatment at different holding times that affect the milk odour. Six samples were acquired from a local dairy goat farm. Approximately 1000 ml were collected from pooled fresh milk for each sampling. Colony count for all treatments presented a reduction in colony number as the holding time was hold longer. However, the result tested statistically non-significant at P>0.05. There are no significant effect (P>0.05) of increasing holding time on nonlactose fermenting bacteria colony in goat milk. The mean CFU is 1.729 ± 0.101 CFU/ml, 1.712 ± 0.039 CFU/ml, 1.529 ± 0.051 CFU/ml and 1.464 ± 0.095 CFU/ml for 0 minutes, 15 minutes, 30 minutes and 45 minutes respectively. The isolates were confirmed as pseudomonads because of their ability to hydrolyse the 3% hydrogen peroxides as evidenced from their positive bubbling reaction. In conclusion, the effect of longer holding times on bacterial load in fresh goat milk is not very significant as it is also influenced by other factors.